ISOLATION, SCREENING AND IDENTIFICATION OF Bacillus sp. PRODUCING ALKALINE PROTEASE - M. M. Omar,; H. A. Jabber, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Twenty-five bacteria isolates (Bacillus sp.) were isolated from different local sources (soil of college of Agriculture/university of Baghdad and from Amiriya); the obtained isolates were screened for their capabilities for producing alkaline proteases. It has been noticed that isolates designated (2,5,6,8,11,12 at 37°C) and (14,17 and 18 at 55°C) were showed high capability for producing alkaline protease. All isolates subjected to secondary screening. The results revealed that isolate (12) coded MH12 was the highest producers with enzyme activity of (81.00U/ml). The Identification tests of this isolate were carried out by studying morphological, microscopic characteristic and using of Vitek2 compact system. These tests were conformed by identification of 16S rRNA gene using PCR and its nitrogen base sequencing and the results revealed that the isolate was belongs to Bacillus cereus.